2011
DOI: 10.1016/j.ygyno.2011.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment and retention results for a population-based cervical cancer biobehavioral clinical trial

Abstract: Background Minority and low-income cancer patients are underrepresented in clinical trials, contributing to diminished access to state-of-the-art care and disparities in cancer outcomes including survivorship issues. In cervical cancer, there is a disproportionate disease burden among minority and underserved women and persistent quality of life disruption. We encountered significant challenges in both recruitment and retention in a randomized biobehavioral clinical trial for cervical cancer survivors, identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…Indeed, studies using the PEN-3 model demonstrated how cultural context matters when developing interventions and/or clinical trials focused on addressing health behaviors such as nutrition attitudes (James 2004; Airhihenbuwa et al 1996), depression prevention (Saulsberry et al 2013), domestic violence (Yick and Oomen-Early 2009), HIV and AIDS (Airhihenbuwa et al 2009; Iwelunmor, Zungu, and Airhihenbuwa 2010; Okoror et al 2012; Westmaas et al 2012; Green et al 2009; Mieh, Iwelunmor, and Airhihenbuwa 2013), reproductive desires (Sofolahan and Airhihenbuwa 2012, 2013), physical inactivity, stress (Gaston, Porter, and Thomas 2007), smoking (Beech and Scarinci 2003; Matthews, Sánchez-Johnsen, and King 2009; Scarinci et al 2007), and cancer screening and awareness (Erwin et al 2010; Osann et al 2011; White et al 2012). …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, studies using the PEN-3 model demonstrated how cultural context matters when developing interventions and/or clinical trials focused on addressing health behaviors such as nutrition attitudes (James 2004; Airhihenbuwa et al 1996), depression prevention (Saulsberry et al 2013), domestic violence (Yick and Oomen-Early 2009), HIV and AIDS (Airhihenbuwa et al 2009; Iwelunmor, Zungu, and Airhihenbuwa 2010; Okoror et al 2012; Westmaas et al 2012; Green et al 2009; Mieh, Iwelunmor, and Airhihenbuwa 2013), reproductive desires (Sofolahan and Airhihenbuwa 2012, 2013), physical inactivity, stress (Gaston, Porter, and Thomas 2007), smoking (Beech and Scarinci 2003; Matthews, Sánchez-Johnsen, and King 2009; Scarinci et al 2007), and cancer screening and awareness (Erwin et al 2010; Osann et al 2011; White et al 2012). …”
Section: Resultsmentioning
confidence: 99%
“…(Linke, Gallo, & Norman, 2011; Moroshko, Brennan, & O'Brien, 2011; Neve, Collins, & Morgan, 2010; Peels et al, 2012) Nonetheless, future physical activity interventions should make every effort to retain participants with, for example, a higher BMI at baseline, by including strategies/messages that directly address issues important to this subgroup (i.e., being physically active is important regardless of how much you weigh or whether you are trying to lose weight or not). Also, lower retention rates for ethnic minorities in randomized clinical trials are a concern;(Arikawa, O'Dougherty, Kaufman, Schmitz, & Kurzer, 2012; Moroshko et al, 2011; Murphy & Williams, 2013; Osann et al, 2011) however, we used several strategies that have been shown to maximize retention in clinical trials (i.e., establishing rapport, participants’ perception of the study as informative, etc. )(Barnett, Aquilar, Brittner, & Bonuck, 2012; D.…”
Section: Discussionmentioning
confidence: 99%
“…Women who felt that their schedules were already too full or who had significant concerns about commuting to and from a treatment site expressed unwillingness to participate in a trial. Other studies have found that female cancer survivors cite being “too busy” as a major reason for declining to participate in trials (20). Addressing the practical barriers to participation (e.g., offering free parking, setting up satellite sites to reduce the commute, and minimizing scheduling requirements) is important as part of a strategy to encourage participation in clinical trials.…”
Section: Discussionmentioning
confidence: 99%